2012
DOI: 10.1007/s00122-012-1866-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and linkage disequilibrium features in a composite public/private dent maize panel: consequences for association genetics as evaluated from a case study using flowering time

Abstract: Recent progress in genotyping and resequencing techniques have opened new opportunities for deciphering quantitative trait variation by looking for associations between traits of interest and polymorphisms in panels of diverse inbred lines. Association mapping raises specific issues related to the choice of appropriate (i) panels and marker-densities and (ii) statistical methods to capture associations. In this study, we used a panel of 314 maize inbred lines from the dent pool, composed of inbred material fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…According to the Hill and Weir model, LD dropped below 0.1 after 200 kb at the genome level and dropped to almost the background level at around 500 kb-1 Mb. This value was in the range of those reported in the literature for different types of panels [85], [86], [87], [88] and illustrates that linkage disequilibrium in maize has markedly increased as a result of domestication [1] and genetic improvement [2], [74], [89]. We observed that the extent of LD varied among chromosomes, i.e.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…According to the Hill and Weir model, LD dropped below 0.1 after 200 kb at the genome level and dropped to almost the background level at around 500 kb-1 Mb. This value was in the range of those reported in the literature for different types of panels [85], [86], [87], [88] and illustrates that linkage disequilibrium in maize has markedly increased as a result of domestication [1] and genetic improvement [2], [74], [89]. We observed that the extent of LD varied among chromosomes, i.e.…”
Section: Discussionsupporting
confidence: 82%
“…This value was in the upper range of those reported by other diversity analyses based on SNP genotyping, ranging from 0.27 to 0.39 [72], [73], [74], [75], [76]. Only eight percent of markers appeared to be monomorphic, showing that some rare alleles discovered with the Panzea panel used to build the 50K Illumina array were not represented in our panel.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…However, these values are not common and could be the result of the specific breeding processes to which this population has been submitted. Other studies with corn report the extent of LD to be low, with rapid decay over physical distances between locations, with a varying range in most cases between 0.5 and 7.0 kb (Remington et al., 2011; Truntzler et al., 2012).…”
Section: Discussionmentioning
confidence: 97%
“…One of the major flowering-time QTL, Vegetative to generative transition 1 ( Vgt1 ) (Phillips et al 1992; Vlăduţu et al 1999; Salvi et al 2002) on chromosome 8, corresponds to a ≈2-kb intergenic region upstream of an Ap2 -like flowering-time gene, ZmRap2.7 and appears to act as a cis -regulator of ZmRap2.7 expression (Salvi et al 2007). A maize–sorghum–rice evolutionarily conserved noncoding sequence (CNS) (Freeling and Subramaniam 2009) was identified within Vgt1 ; in early Vgt1 alleles, this CNS is interrupted by the insertion of a miniature transposon (MITE) belonging to the Tourist family (Salvi et al 2007), and this insertional polymorphism has been repeatedly identified as strongly associated with flowering time in independent studies (Salvi et al 2007; Ducrocq et al 2008; Buckler et al 2009; Hung et al 2012; Truntzler et al 2012). …”
mentioning
confidence: 99%